Exploring the role of the WNT5A rs566926 polymorphism and its interactions in non-syndromic orofacial cleft: a multicenter study in Brazil - Lorraynne dos Santos LARA; Ricardo D. COLETTA; Renato Assis MACHADO; Lilianny Querino Rocha de OLIVEIRA; Hercílio MARTELLI JÚNIOR; Silvia Regina de Almeida REIS; Rafaela SCARIOT; Luiz Evaristo Ricci VOLPATO (University of São Paulo, 2024)
Abstract Associations between the WNT5A rs566926 variant and non-syndromic orofacial cleft (NSOC) have been reported in different populations. Objective This study aimed to investigate the role of the rs566926 single nucleotide polymorphism (SNP) in WNT5A and its interactions with SNPs in BMP4, FGFR1, GREM1, MMP2, and WNT3 in the occurrence of NSOC in a Brazilian population. Methodology A case-control genetic association study was carried out involving participants from four regions of Brazil, totaling 801 patients with non-syndromic cleft lip with or without cleft palate (NSCL±P), 273 patients with cleft palate only (NSCPO), and 881 health volunteers without any congenital condition (control). Applying TaqMan allelic discrimination assays, we evaluated WNT5A rs566926 in an ancestry-structured multiple logistic regression analysis, considering sex and genomic ancestry as covariates. Interactions between rs566926 and variants in genes involved in the WNT5A signaling pathway (BMP4, FGFR1, GREM1, MMP2, and WNT3) were also explored. Results WNT5A rs566926 was significantly associated with an increased risk of NSCL±P, particularly due to a strong association with non-syndromic cleft lip only (NSCLO), in which the C allele increased the risk by 32% (OR: 1.32, 95% CI: 1.04-1.67, p=0.01). According to the proportions of European and African genomic ancestry, the association of rs566926 reached significant levels only in patients with European ancestry. Multiple interactions were detected between WNT5A rs566926 and BMP4 rs2071047, GREM1 rs16969681 and rs16969862, and FGFR1 rs7829058. Conclusion The WNT5A rs566926 polymorphism was associated with NSCL±P, particularly in individuals with NSCLO and high European ancestry. Epistatic interactions involving WNT5A rs566926 and variants in BMP4, GREM1, and FGFR1 may contribute to the risk of NSCL±P in the Brazilian population.